104k views
13 votes
If f(x)=3x²-5x+4, then f(-2) =

User Imekon
by
5.1k points

1 Answer

10 votes

Answer:

Explanation:

First let's re-write the equation:

f(x) = 3x² - 5x + 4

If f(-2). then we can re-write the equation as:

f(-2) = 3(-2)² - 5(-2) + 4

We must solve for exponent first: (-2)² = 4

f(-2) = 3(4) - 5(-2) + 4

Then solve for multiplication:

f(-2) = 12 + 10 + 4

Finally addition:

f(-2) = 26

that means that in a function, if X = -2, then F is equal to 26

User Wonderflame
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.